DOL SEBAGAI IDE PENCIPTAAN TAS MAKE UP - Rusmiati, Rusmiati; Widdiyanti, Widdiyanti; Prastawa, Wisnu (Relief : Journal of Craft, 2023)
Dol is a traditional Bengkulu musical instrument resembling a bedug, which is played by striking using a wooden bat with a cloth-covered end. The Dol instrument is tubular with a slightly oblong bottom and has a single membrane as the sound source at the top. The body is painted in bright hues like red, green, and yellow to make it more appealing. Its distinctive form inspired the development of textile products in the form of makeup bags. Ornamentation of works using the batik techniques. The process used to create this artwork involves three stages: exploration, seeking sources of knowledge on dol musical instruments; design, which entails creating drawings for the work; embodiment, which consists of the writing batik technique and stitching the bag. The five pieces of original artwork and two pieces of designed artwork are combined to form a makeup bag. Each work is titled according to the type of rhythm in playing dol namely Suwena 1, Suwena 2, Suwari 1, Suwari 2, Suwari 3, Tamatam 1, and Tamatam 2.